1996
DOI: 10.1001/archsurg.1996.01430220080018
|View full text |Cite
|
Sign up to set email alerts
|

Local Irrigation With Tissue Factor Pathway Inhibitor Inhibits Intimal Hyperplasia Induced by Arterial Interventions

Abstract: Local irrigation with TFPI at the time of arterial interventional therapy inhibits intimal hyperplasia following either balloon angioplasty or intimectomy. We hypothesize that TFPI binds to the injured vessel surface and inhibits the cascade of thrombotic events that promote intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…It is possible that increased TF expression at injured atherosclerotic coronary lesions enhances thrombin generation in the coronary circulation. Several previous studies demonstrated that inhibition of TF binding to other coagulation factors prevented restenosis of balloon-injured arteries in animal models [31, 32, 33]. Inhibition of initiation of the extrinsic coagulation pathway was suggested to be important in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased TF expression at injured atherosclerotic coronary lesions enhances thrombin generation in the coronary circulation. Several previous studies demonstrated that inhibition of TF binding to other coagulation factors prevented restenosis of balloon-injured arteries in animal models [31, 32, 33]. Inhibition of initiation of the extrinsic coagulation pathway was suggested to be important in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant TFPI can prevent thrombosis and restenosis after arterial injury in cell culture systems in vitro and in various animal models. [81][82][83][84][85][86][87][88][89][90][91][92] There are also reports that endogenous TFPI is involved in the process of thrombus formation in vivo and that it plays an active role in modulating arterial stenosis. 93 These results indicate that the intravenous administration of recombinant TFPI protein prevents thrombosis at an early stage and restenosis at a later stage.…”
Section: Potential Roles Of Tfpi In Atherogenesismentioning
confidence: 99%
“…25 The failure of systemically administered antithrombotic therapy to efficiently interfere with clinical postangioplasty restenosis in humans is thought to be a result of insufficient local concentration of antithrombotic drugs at sites of balloon injury. Thus, various studies with local application strategies of TFPI protein 23,24,[26][27][28][29][30][31] or TFPI gene [32][33][34][35] were undertaken to antagonize local thrombus formation, intimal hyperplasia, or vascular remodeling, generally using a surgical approach for irrigation or transfection. In contrast to these studies, we sought to locally overexpress TFPI using a clinically feasible, catheter-based approach.…”
mentioning
confidence: 99%